Alexa for seniors in easy steps - Vandome, Nick (In easy steps., 2020)
Provides instructions for seniors on how to use Alexa, Amazon's voice-controlled digital personal assistant, to perform a range of everyday tasks, including setting and controlling smart home devices such as smart heating and smart lighting, making hands-free phone calls, and shopping online.